Evaluation of Olfactory Bulb Volumes in Patients With Rheumatoid Arthritis: A Retrospective Study - Selçuk SAYILIR; Neşat ÇULLU; Gönen MENGİ and Timur EKİZ (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate olfactory bulb (OB) volume in patients with rheumatoid arthritis (RA) using magnetic resonance imaging. Patients and methods: In this retrospective and case-control study, OB volumes of 37 RA patients (6 males, 31 females; mean age 48.6±10.8 years; range, 18 to 65 years) were compared with those of 36 healthy control subjects (5 males, 31 females; mean age 46.5±6.9 years; range, 22 to 62 years). OB images were gained with a protocol of 256×256 matrix and a 24-cm field of view, repetition time=5000 milliseconds (TR 5000 msec), echo time=130 milliseconds (TE 130 msec), number of excitations=2 (NEX 2) and a 5 mm slice thickness. OB volume was computed with the aid of the above images using three dimensional views. The surface of each slice area was calculated in mm2 and all surfaces were added and multiplied by front-back length to obtain a volume in mm3. Results: Left (70.5±14.4 vs. 91.1±12.2 mm3), right (73.9±15.1 vs. 91.2±12.4 mm3), and total (144.5±27.4 vs. 182.8±21.5 mm3) OB volumes were significantly lower in the RA group than in the control group (all p<0.05). Conclusion: Patients with RA may be under risk of decreased OB volumes and related impaired odor functions which might affect the quality of life and activities of daily living adversely.